Rapeseed meal hydrolysate as substrate for microbial astaxanthin production - Tuan Harith, Zuharlida; Charalampopoulos, Dimitris; Chatzifragkou, Afroditi (Elsevier, 2019)
Rapeseed meal, a by-product of oil processing industry, was evaluated as a substrate for astaxanthin production by the yeast Xanthophyllomyces dendrorhous DSMZ 5626. Four commercial enzymes were tested at different concentrations (1–15%, v/v) for their ability to break down the cellulosic and hemicellulosic compounds of rapeseed meal into fermentable sugars. Viscozyme® L and cellulase demonstrated the highest glucose recovery yields (47–52%, w/w for 15% (v/v) of enzyme loading) with 7–11 g/l of net glucose released in the hydrolysates. Pectinase and Accellerase® hydrolysates supported the best cell growth and astaxanthin production in batch shake flask cultures, with maximum biomass of 26 g/l and 15 g/l, respectively, and astaxanthin yields (YP/X) of 258–332 μg per g of biomass. In batch bioreactor trials, pectinase hydrolysates resulted in high biomass (42 g/l) and astaxanthin production (11 mg/l) aided by the presence of glycerol (originating from the enzyme formulation) which served as additional energy and carbon source. Finally, simple glass beads disruption lead into satisfactory astaxanthin extraction (95%, w/w) in acetone. The findings of this study generate knowledge towards scale-up potential of microbial astaxanthin production using rapeseed meal hydrolysate as fermentation feedstock.